Prehospital use of hemostatic dressings by the Israel Defense Forces Medical Corps: A case series of 122 patients. (October 2015) - Shina, Avi; Lipsky, Ari M.; Nadler, Roy; Levi, Moran; Benov, Avi; Ran, Yuval; Yitzhak, Avraham; Glassberg, Elon
Abstract : BACKGROUND: Hemostatic dressings are advanced topical dressings designed to control hemorrhage by enhancing clot formation. These dressings may be effective when used on injuries sustained in junctional zones. The Israeli Defense Forces Medical Corps (IDF-MC) chose to equip its medical personnel with the QuikClot Combat Gauze. There is a paucity of data describing clinical use and results of hemostatic dressing especially at the point of injury. The purpose of this article was to report the IDF-MC experience with prehospital use of the QuikClot Combat Gauze in junctional zones in a case series retrieved from the IDF Trauma Registry. METHODS: All IDF Trauma Registry documented cases of prehospital use of hemostatic dressings in the IDF-MC between January 2009 and September 2014 were retrieved. Data collection included injury mechanism, wound location, reported success of hemostatic dressing, tourniquet use, lifesaving interventions, mortality, and caregiver identity. RESULTS: A total of 122 patients on whom 133 hemostatic dressings were applied were identified. Median age was 22 years. Of the patients, 118 (96.7%) were male and 2 (1.6%) were female (missing, n = 2). Injury mechanism was penetrating in 104 (85.2%), blunt in 4 (3.3%), and combined in 14 (11.5%) patients. Seven patients (5.9%) died. Thirty-seven dressings (27.8%) were used for junctional hemorrhage control (pelvis, shoulder, axilla, buttocks, groin, neck), and 92 dressings (72.1%) were placed in nonjunctional areas (missing, n = 4). Nonjunctional dressings included 63 (47.4%) applied to the extremities, 14 (10.5%) to the back, and 4 (3%) to the head. Hemostatic dressing application was reported as successful in 88.6% (31 of 35 available; missing, n = 2) of junctional hemorrhage applications and in 91.9% (57 of 62 available; missing, n = 1) of extremity hemorrhage applications. CONCLUSION: Hemostatic dressings seem to be an effective tool for junctional hemorrhage control and should be considered as a second-line treatment for extremity hemorrhage control at the point of injury. LEVEL OF EVIDENCE: Therapeutic study, level V.